A Sociotechnical Framework for Governing Climate Engineering. (March 2016) - Bellamy, Rob
Proposed ways of governing climate engineering have most often been supported by narrowly framed and unreflexive appraisals and processes. This article explores the governance implications of a Deliberative Mapping project that, unlike other governance principles, have emerged from an extensive process of reflection and reflexivity. In turn, the project has made significant advances in addressing the current deficit of responsibly defined criteria for shaping governance propositions. Three such propositions argue that (1) reflexive foresight of the imagined futures in which climate engineering proposals might reside is required; (2) the performance and acceptance of climate engineering proposals should be decided in terms of robustness, not optimality; and (3) climate engineering proposals should be satisfactorily opened up before they can be considered legitimate objects of governance. Taken together, these propositions offer a sociotechnical framework not simply for governing climate engineering but for governing responses to climate change at large.